Trapped or staying put: Governing immobility in the context of climate change - Thornton, Fanny; Serraglio, Diogo Andreolla; Thornton, Alec (Frontiers in Climate, 2023)
By presenting a range of outcomes which result from the impacts of a changing environment on human mobility patterns, the Foresight Report on Migration and Global Environmental Change (2011) emphasised that, whereas some people choose to stay in a specific location, others are simply unable to leave, leading to what the report termed ‘trapped populations’. Much understanding about both voluntary and involuntary immobility in the context of environmental or climatic change has been gained since. The IPCC’s recent report (2022) on climate change impacts, vulnerabilities and adaptation further underlined that, in the decades ahead, some people will be unable or unwilling to move away from locations in which they may nevertheless be vulnerable to the impacts of climate change. What has received less attention is how climate immobility ought to be governed and which norms should underpin its governance. In this paper, we rely on select existing law and policy instruments and frameworks from Latin American and the Pacific Islands regions to outline key considerations of a governance structure suitable for (in)voluntary immobility. This will inform individuals, communities, and policy makers who seek to navigate through complex reasons and decisions for ‘staying put’ or ‘getting stuck’ in the face of climatic change. The analysis builds upon a review of published literature and, especially, existing policy and legal frameworks at national and regional levels. We argue that a more widespread, timely and proactive approach to policy and governance is required in support of resilience in the context of climate immobility.